Regulation of Network Condensation Based on Fitness Ordered Access Strategy - Xu, Dongpeng (AI Society & STMIK Indonesia, 2024)
The condensation in complex networks disclose the underlying mechanism of the monopoly in socioeconomic system, which can help us to design and access the anti-monopoly policy based on the study on network condensation. Inspired by the consideration, We introduce a set of rearrangement mechanism into the fitness model to regulate the order of nodes with different fitness to enter the network, and study the influence of this regulation strategy on network condensation. By extensive Monte Carlo simulations and finite size scaling analysis, we obtain the critical rearrangement index under a typical fitness distribution, establish the relationship between the index and the condensation intensity, and finally construct the condensation phase diagram. These results show that there exists an interval of the critical rearrangement index, outside which the condensation of the fitness model will be effectively suppressed. We carry out a theoretical analysis on some key results to understand their underlying origin, and discuss their instructive significance on the anti-monopoly market management.